Cervicovaginal specimen biomarkers for early detection of ovarian and endometrial cancer: A review - Kevin J. J. Kwinten; Victor A. Lemain; Joanne A. deHullu; William P. J. Leenders; Miranda P. Steenbeek; Anne M. vanAltena; Johanna M. A. Pijnenborg (Cancer Medicine)
Abstract Background In the last decade, technical innovations have resulted in the development of several minimally invasive diagnostic cancer tools. Within women at high risk of developing ovarian cancer (OC) or endometrial cancer (EC) due to a hereditary cancer syndrome, there is an urgent need for minimally invasive and patient‐friendly methods to detect OC and EC at an early stage. Materials and Methods We performed a systematic search of studies using DNA methylation or mutation analysis, microbiome, or proteomics performed on cervicovaginal specimens (smear, swab, or tampon) intended to detect OC and EC published until January 2024. Results Included studies (n = 36) showed high heterogeneity in terms of biomarkers used and outcomes, and only a few studies reported on the detection of biomarkers in high‐risk subgroups. Conclusion Based on the findings in this review, DNA methylation techniques seem to be the most promising for detecting OC and EC at early stages in the general population. Future validation of cervicovaginal DNA methylation techniques is needed to determine whether this technique might be beneficial in hereditary high‐risk subgroups.